(untitled) (Materiali di Estetica. Terza serie, 2022)
The philosophical school of Milan has always paid a great attention to the international relationships. We examine here the case of the publication of Ricoeur’s De l’interprétation. This text was the object of great controversies in France, but was uphold in Italy by Enzo Paci and his school. They were able to highlight some innovative aspects of the discourse and in particular the connection between phenomenology and psychoanalysis, connection linked to the intersubjective dimension